Fenomena Pasca-Kebenaran: Belajar dari Sejarah, Menyongsong Tahun Politik 2024 - Mahardika, Amadea Prajna Putra (Fakultas Teologi, Universitas Sanata Dharma, 2024)
This writing aims to dissect several aspects of the Post-Truth phenomenon in general, including its definition, the reasons behind its emergence, its elements or characteristics, as well as its impacts. To make it easier to comprehend, real-life examples will be provided, both in the political and mass media spheres, which happened both internationally and within Indonesia. In this research, we use qualitative method through literature and internet review. Learning from history, the Post-Truth phenomenon is rampant during political campaigns leading up to elections. Therefore, as the year 2024 approaches, a significant political year in Indonesia, efforts need to be made to anticipate the negative impacts of Post-Truth. These negative consequences can foster distrust in society, provide opportunities for irresponsible individuals to take advantage, and potentially threaten the stability, security, and unity of the nation. To address this issue, all parties and authorities involved must collaborate and employ a multidimensional approach called the